Perancangan Buku Ilustrasi Tradisi Peusijuk Pada Masyarakat Aceh Sebagai Media Informasi Bagi Kalangan Remaja - Isman, Soeryadarma; Muliati, Roza; Juned, Sulaiman (Laga-Laga : Jurnal Seni Pertunjukan, 2025)
The Peusijuk tradition is one of the cultural heritages of the Acehnese people that contains religious, social, and symbolic values. However, technological developments and the influence of globalization have caused the younger generation to increasingly know and understand less of the meaning of this tradition. Therefore, media that is interesting and in accordance with the character of teenagers is needed to reintroduce the Peusijuk tradition in an educational and visual way. This study aims to design an illustrated book that packages information about the Peusijuk tradition in a communicative, interesting, and easy-to-understand way for teenagers. The methods used include observation, interviews, literature studies, and distributing questionnaires. The result is an illustrated book that tells stories of Acehnese children engaging in Peusijuk traditions with supporting media like posters, pins, keychains, and digital content. The book is expected to serve as an effective cultural education tool and promote the preservation of local traditions.